NEW FORMS OF TEMPORARY EMIGRATION FROM RUSSIA - Sergey Ryazancev (Наука. Инновации. Технологии)
This paper examines the theoretical approaches to the definition of "temporary migration". Highlighted new forms of temporary emigration from Russia, which were developed after the collapse of the USSR. We gave approximate statistical estimates of the number of flows of temporary labor migration. We proposed definition of each of the flows of temporary labor migrants from Russia, recommendations to improve Russia's policy towards temporary emigration.